Moby-duck : the true story of 28,800 bath toys lost at sea and of the beachcombers, oceanographers, environmentalists, and fools, including the author, who went in search of them - Hohn, Donovan (Viking, 2011)
When the author heard of the mysterious loss of thousands of bath toys at sea, he figured he would interview a few oceanographers, talk to a few beachcombers, and read up on Arctic science and geography. But questions can be like ocean currents: wade in too far, and they carry you away. His accidental odyssey pulls him into the secretive world of shipping conglomerates, the daring work of Arctic researchers, the lunatic risks of maverick sailors, and the shadowy world of Chinese toy factories. This work is a journey into the heart of the sea and an adventure through science, myth, the global economy, and some of the worst weather imaginable. With each new discovery, he learns of another loose thread, and with each successive chase, he comes closer to understanding where his castaway quarry comes from and where it goes.